2015
DOI: 10.1007/s00267-015-0553-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Agricultural and Ecological Goals into the Management of Species-Rich Grasslands: Learning from the Flowering Meadows Competition in France

Abstract: Current agri-environmental schemes for reconciling agricultural production with biodiversity conservation are proving ineffective Europe-wide, increasing interest in results-based schemes (RBSs). We describe here the French "Flowering Meadows" competition, rewarding the "best agroecological balance" in semi-natural grasslands managed by livestock farmers. This competition, which was entered by about a thousand farmers in 50 regional nature parks between 2007 and 2014, explicitly promotes a new style of agri-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…; Magda et al . ). However, these schemes can potentially punish farmers who act adequately but do not achieve the goals because of external variables, such as land configuration (e.g.…”
Section: How To Promote or Support Ecological Intensification In Policymentioning
confidence: 97%
See 1 more Smart Citation
“…; Magda et al . ). However, these schemes can potentially punish farmers who act adequately but do not achieve the goals because of external variables, such as land configuration (e.g.…”
Section: How To Promote or Support Ecological Intensification In Policymentioning
confidence: 97%
“…Recently, it was suggested that switching to 'payment by results schemes' (i.e. paying farmers for outcomes rather than for performing set management activities) could be an effective instrument for changing farming social behaviour, and could encourage the establishment of common goals between farmers and conservationists (de Snoo et al 2012;Magda et al 2015). However, these schemes can potentially punish farmers who act adequately but do not achieve the goals because of external variables, such as land configuration (e.g.…”
Section: How To Promote or Support Ecological Intensification In Policymentioning
confidence: 99%
“…Two studies also demonstrate that compromises between intensive production and biodiversity conservation (including forest landscape connectivity) or environmental parameter preservation are possible at the landscape scale (Marusak et al 2015;Tittler et al 2015), which strengthens the idea of implementing EI at different spatial scales (Tittonell 2014). Finally, it appears that the possibility of reconciling production and the environment requires avoiding opposing these two elements in concepts and speech; building interactive and reflexive interactions between researchers, owners, and managers; and building landscape agroecosystem designs based on innovation, cooperation, and intensive knowledge sharing (Lemaire et al 2015;Levain et al 2015;Magda et al 2015; see also Tittonell (2014) and Caron et al (2014)). …”
mentioning
confidence: 88%
“…It contains innovative scientific research focusing on the following topics related to EI: (1) the relationships between specific practices and key functional ecological components or biodiversity (Kershaw et al 2015); (2) the efficiency of practices according to EI principles (Lemaire et al 2015;Levain et al 2015;Mattioli et al 2015;Petit et al 2015;Podadera et al 2015); and (3) the analysis of trade-offs and synergies between production and biodiversity conservation (Lafond et al 2015;Loucougaray et al 2015;Magda et al 2015;Marusak et al 2015;Mathias et al 2015;Tittler et al 2015).…”
mentioning
confidence: 99%
“…In the context of implementing green belt provisions, farmers are faced with the challenge of ensuring a profitable production while at the same time following the rules set up to protect biodiversity. Moreover, while the landscape transformations leading to fragmented habitats are caused by multiple factors such as urban sprawl, expanding transport infrastructures, increasing traffic, land consolidation and draining of wetlands, modern intensive farming is often pointed to as a major driver of the collapse of wildlife populations and a threat to biodiversity conservation (Jongman, 2002;Henle et al, 2008), when in fact there are possible synergies between agriculture and biodiversity (Altieri, 1999;Grashof-Bokdam and Van Langervelde, 2004;Le Roux et al, 2008;Fleury et al, 2015;Magda et al, 2015).…”
Section: Background and Issuesmentioning
confidence: 99%